2023
DOI: 10.3390/antibiotics12020308
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Utilization during COVID-19: Are We Over-Prescribing?

Abstract: The aims of this study were to analyze the utilization of antibiotics before (2018, 2019) and during the COVID-19 pandemic (2020) and the practice of prescribing antibiotics in outpatient settings for COVID-19 patients during the 2020–2022 period. The Anatomical Therapeutic Chemical Classification/Defined Daily Dose methodology was used for the analysis of outpatient antibiotic utilization in the Republic of Srpska. The data was expressed in DDD/1000 inhabitants/day. The rate of antibiotics prescribed to COVID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 52 publications
1
13
0
Order By: Relevance
“…While scientific bodies have suggested that azithromycin’s antibacterial and anti-inflammatory properties may be useful in the empirical treatment of pulmonary co-infections in COVID-19 patients, the evidence for its direct activity in COVID-19 has been largely inconclusive [ 83 , 84 ]. Although clinical trials, such as RECOVERY, PRINCIPLE, and COALITION II, showed the lack of efficacy of azithromycin on clinical outcomes [ 85 , 86 , 87 ], several studies confirmed that azithromycin was the most commonly prescribed antibiotic during the COVID-19 pandemic [ 88 , 89 , 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…While scientific bodies have suggested that azithromycin’s antibacterial and anti-inflammatory properties may be useful in the empirical treatment of pulmonary co-infections in COVID-19 patients, the evidence for its direct activity in COVID-19 has been largely inconclusive [ 83 , 84 ]. Although clinical trials, such as RECOVERY, PRINCIPLE, and COALITION II, showed the lack of efficacy of azithromycin on clinical outcomes [ 85 , 86 , 87 ], several studies confirmed that azithromycin was the most commonly prescribed antibiotic during the COVID-19 pandemic [ 88 , 89 , 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for this trend are uncertain. However, this may demonstrate the considerable focus on managing patients with COVID-19 in Albania since the start of the pandemic, with this trend matching the increasing use of antibiotics seen in other countries during the pandemic [48,50,51]. This trend is difficult to justify as there is little evidence of bacterial infections in these patients [51,63,64].…”
Section: Discussionmentioning
confidence: 99%
“…Alongside this, we are aware that there has been an appreciable increase in the use of antibiotics in patients with COVID-19 across countries and sectors despite limited evidence of bacterial infections or co-infections [48][49][50][51][52][53], which might represent significant levels of inappropriate use. Consequently, there is also a need to examine antibiotic utilization trends during the pandemic in Albania alongside the implications.…”
Section: Introductionmentioning
confidence: 99%
“…Community consumption of azithromycin, a macrolide, increased during the first year of the pandemic in multiple countries with significant variation across geographic locations and with greatest prescribing among older patients (Bara et al, 2022; Bednarčuk et al, 2023; Bogdanić et al, 2022; Crisafulli et al, 2022; Parveen et al, 2020; Weill et al, 2021). In an outpatient setting in southern Italy between February 2020 and January 2021, azithromycin represented 42.1% of all drug prescriptions to individuals diagnosed with COVID-19, while all other antibiotics combined represented just 20.9% (Crisafulli et al, 2022).…”
Section: Discussionmentioning
confidence: 99%